Use of Foods Based on Bee Drone Brood: Their Sensory and Microbiological Evaluation and Mineral Composition - Borkovcová, Marie; Mlček, Jiří; Adámková, Anna; Adámek, Martin; Bednářová, Martina; Musilová, Zuzana; Ševčíková, Veronika (MDPI, 2022)
The aim of the work was to evaluate the safety of bee drone brood in terms of the risk of possible contamination with heavy metals, microbial contamination, and sensory acceptability. Bee drone brood dried at a temperature of 80 degrees C in a hot air oven (DBO) and lyophilized drone brood (DBL) were used. Sensory evaluation was performed on an oatmeal ball (O-B) and drone brood ball (DBO-B). For the determination of the minerals and other elements in DBO, spectrometric analysis was used. The content was as follows: Fe 60.87 mu g/g, Cu 54.83 mu g/g, Zn 257 mu g/g, Ag 82.7 mu g/g, Pb 2.1 mu g/g, Au 1.2 mu g/g, Ca 1336 mu g/g, Sr 3.13 mu g/g, Zr 1.67 mu g/g, Bi 3.87 mu g/g, Br 1.95 mu g/g. The detected content of lead in dry matter (2.1 mu g/g) was high above the limit set for crustaceans (0.4 mu g/g). By comparing microbial assay values, no statistically significant difference between freshly dried DBO and dried DBO after a month of storage was detected. Bee drone brood contains microbes far below the legal limits and it is a good source of calcium, iron, and zinc. Except for the juiciness, consumers rated O-B better than DBO-B. A statistically significant difference (p < 0.05) was found only in taste.

The aim of the work was to evaluate the safety of bee drone brood in terms of the risk of possible contamination with heavy metals, microbial contamination, and sensory acceptability. Bee drone brood dried at a temperature of 80 degrees C in a hot air oven (DBO) and lyophilized drone brood (DBL) were used. Sensory evaluation was performed on an oatmeal ball (O-B) and drone brood ball (DBO-B). For the determination of the minerals and other elements in DBO, spectrometric analysis was used. The content was as follows: Fe 60.87 mu g/g, Cu 54.83 mu g/g, Zn 257 mu g/g, Ag 82.7 mu g/g, Pb 2.1 mu g/g, Au 1.2 mu g/g, Ca 1336 mu g/g, Sr 3.13 mu g/g, Zr 1.67 mu g/g, Bi 3.87 mu g/g, Br 1.95 mu g/g. The detected content of lead in dry matter (2.1 mu g/g) was high above the limit set for crustaceans (0.4 mu g/g). By comparing microbial assay values, no statistically significant difference between freshly dried DBO and dried DBO after a month of storage was detected. Bee drone brood contains microbes far below the legal limits and it is a good source of calcium, iron, and zinc. Except for the juiciness, consumers rated O-B better than DBO-B. A statistically significant difference (p < 0.05) was found only in taste.
Use of Foods Based on Bee Drone Brood: Their Sensory and Microbiological Evaluation and Mineral Composition
Keywords: bee brood; drone brood; sensory analysis; minerals; microbiological analysis; bee brood; drone brood; sensory analysis; minerals; microbiological analysis